The relationship between smartphone addiction, internet gaming disorder (IGD), and sleeping problem (Insomia) among young undergraduate students in Malaysia - Leong, Lerk Yung; Liew, Yee Hang; Shin, Bin Shyen (2023)
Insomnia is one of the major sleeping disorders that affect millions of people around the world, including Malaysia. Hence, the study aimed to find out the relationship between smartphone addiction, internet gaming disorder, and insomnia among the young undergraduates in Malaysia. There are three instruments that were used in this study to for the measuring of each respective constructs, which are Five-factor Smartphone Addiction Inventory short-form with 10 items (5FSPAI-SF), Internet Gaming Disorder Scale-Short Form (IGDS9-SF), and Insomnia Severity Index (ISI). The quantitative methodology and survey design of cross-sectional were applied for the study. We also apply purposive sampling method to collect respondent from young adults in Malaysia, aged between 18 – 26 years old, who were the major group of people that are affected by insomnia. 162 young adults from Malaysia have responded to the study by filling and answering the survey questionnaire. The results have shown that both smartphone addiction and internet gaming disorder have a positive relationship with insomnia. Both smartphone addiction and internet gaming disorder positively predicted insomnia. The current research not only illuminates new perspectives on insomnia among young undergraduates in Malaysia but also furnishes empirical evidence to policymakers for devising evidence-based programs that address Insomnia.